35‐1: Strategy for Developing an Ultra‐High‐Luminance AMOLED Display. Issue 1 (30th May 2018) - Eguchi, Shingo; Nakamura, Daiki; Kusunoki, Koji; Kawashima, Susumu; Takita, Yusuke; Seo, Satoshi; Dobashi, Masayoshi; Misawa, Chieko; Nakada, Masataka; Yamazaki, Shunpei
Abstract : To obtain a high‐luminance active‐matrix organic light‐emitting diode (AMOLED) display compatible with the high‐dynamic‐range (HDR) technology, we investigated the effect of basic components, e.g., field‐effect transistor, pixel circuit, OLED structure, and organic material. Combining these technologies, we fabricated a high‐luminance display with a peak luminance exceeding 3, 000 cd/m 2 .